The importance of target product engineering for long-term operation of CO2 zero-gap electrolysers. Issue 3 (June 2022) - Duarte, Miguel; Hereijgers, Jonas; Daems, Nick; Van Daele, Sam; Breugelmans, Tom
Abstract: Zero-gap electrolysers lead the race for industrial implementation in the electrosynthesis of carbon-based products from waste CO2 . Due to their compact structure, these reactors have lower ohmic losses and attain higher energy efficiencies than the alternatives. However, most research conducted on these electrochemical cells dismisses key product-specific considerations. In this work, we optimised a zero-gap system and tuned it for the production of both formate and carbon monoxide. We assessed the industrial applicability of alternative metal-nitrogen-doped carbon catalysts and benchmarked them with state-of-the-art metallic nanoparticles. We achieved energy efficiencies as high as 50.4% for the production of HCOO - and 58.0% for the production of CO (86.9 mA cm −2 ). Finally, a rapid degradation study was conducted for start-stop operation, which revealed the current challenges of this novel family of catalysts. This study constitutes an essential step in the direction of upscaled zero-gap CO2 electrolysis with metal-nitrogen-doped carbon catalysts. Graphical Abstract: ga1 Highlights: High selectivity of metal-nitrogen-doped carbons towards HCOO - and CO was successfully replicated in zero-gap conditions. Ion exchange membrane, water injection and flow channel dimensions were tailored for CO and HCOO - reaction sensitivities. Energy efficiencies as high as 50.4% for the production of HCOO - and 58.0% for the production of CO were achieved −2 . Weaknesses of MNC catalysts regarding stability under start-stop operation in MEAs were exposed.